2020
DOI: 10.3390/app10248835
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Acoustic Communication Using Differential Chirp Spread Spectrum

Abstract: Here, we propose a new modulation method using chirp spread spectrum (CSS) modulation to indicate the result of long-range acoustic communication (LRAC). CSS modulation had outstanding matched filter characteristics even though the channel was complex. The performance of the matched filter depends on the time–bandwidth product. We studied the method of using the same modulation method while increasing the amount of the time–bandwidth product. When differential encoding is applied, the de-modulation is made usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…FB methods are based on the identification of defining features capable of discriminating between the analyzed signals. The most used features in FB scenarios are given by instantaneous features (Yu et al, 2019), high-order statistical features (Xiao-Ming and Zhong-Zhao, 2006), wavelet features (Huang et al, 2010) and time-frequency representations (Lee et al, 2020;Khan et al, 2022). But the performance of these FB methods largely depends on empirical feature extraction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…FB methods are based on the identification of defining features capable of discriminating between the analyzed signals. The most used features in FB scenarios are given by instantaneous features (Yu et al, 2019), high-order statistical features (Xiao-Ming and Zhong-Zhao, 2006), wavelet features (Huang et al, 2010) and time-frequency representations (Lee et al, 2020;Khan et al, 2022). But the performance of these FB methods largely depends on empirical feature extraction.…”
Section: Introductionmentioning
confidence: 99%
“…The thresholds used in this approach can be an impediment, because the choice of values is not automatic. The CSS signal recognition was improved in (Lee et al, 2020) by using the matched filter method on the spectrogram approach. The authors showed that the size of the matched filter can be doubled by applying a differential coding method and the performance is improved even if the SNR value is SNR 0dB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, such systems may use a multi-antenna technique [ 12 , 13 ]. The most popular representatives of the spread spectrum technique are frequency-hopping spread spectrum (FHSS), direct-sequence spread spectrum (DSSS), and chirp spread spectrum (CSS), although there are also several variations [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Among them, there are mainly systems with solutions that ensure data transmission with the highest possible transmission rate in vertical channels and a relatively lower rate in horizontal channels.…”
Section: Introductionmentioning
confidence: 99%
“…Interference cancellation is crucial for underwater communication, this topic has been addressed by Diamant [ 43 ]. In the more recent work of Lee et al [ 44 ], the authors explore the parameter space of chirp spread spectrum (CSS) methods in context of long range communication.…”
Section: Introductionmentioning
confidence: 99%